Application of quantitative mineralogy to determine sources of airborne particles at a European copper smelter. Issue 3 (March 2023) - Kelvin, Michelle; Verpaele, Steven; Gopalapillai, Yamini; Poland, Craig; Leybourne, Matthew I.; Layton-Matthews, Daniel
Abstract: Copper processing operations, such as smelters and refineries, can produce airborne particles that may impact the health of workers. At these operations, worker exposure to chemicals are regularly monitored to ensure that regulatory compliance with occupational exposure limit values (OELVs) are maintained. Determining the type of airborne particles present is important for characterizing the composition of dust exposures and better understanding the relationship between worker exposure and health. Routine methods of analysis (e.g., chemical assay) are unable to differentiate between phases containing the same elements and may result in ambiguity. A novel approach of a combination of Quantitative Evaluation of Materials by Scanning Electron Microscope (QEMSCAN) and chemical characterization was used here to evaluate airborne and settled dust collected at key locations throughout a copper smelter in Europe. The copper (Cu) phases present in the airborne dust are indicative of the activities performed at specific locations. In the batch preparation area where Cu concentrate is received, significant amounts of Cu were carried in sulfidic minerals (chalcocite, chalcopyrite/bornite, >40%), whereas near the anode and electric furnace, the majority of Cu in dust was carried in metallic and oxidic phases (60–70%). Particle size analysis of the settled dust indicates that the sulfidic and oxidic Cu minerals are more likely to become airborne over metallic Cu. Furthermore, overall Cu concentrations decreased with particle size where metallic and oxidic Cu dominate, which suggests that differences in the proportion of Cu forms present in the dust will impact how much Cu ends up in the respirable fraction. These results highlight the need to understand the characterization of Cu in dust in order to set better OELVs.